Relationship between prenatal anxiety, depression, pregnancy stress and their social determinants - Weicui Meng; Sufeila Shalayiding; Xiaoting Wang; Bahedana Sailike; Ting Jiang (BMC Psychology)
Abstract Background Prenatal anxiety, prenatal depression, and pregnancy-related stress are prevalent among pregnant women. Across China, the prevalence rates of antenatal depression, anxiety, and pregnancy-related stress are 12.07–36.4%, 16%, and 94.48% respectively. As the most common psychological issues during pregnancy, these three often coexist, interweave, and form a vicious cycle. Social determinants refer to broad social, economic, political, psychosocial, and behavioral factors that directly or indirectly influence health outcomes. A large body of evidence indicates that social determinants are significantly associated with mental health outcomes. However, no studies have yet explored the network relationships among these three conditions and their social determinants in Urumqi, Xinjiang, China. Given that psychological problems during pregnancy may lead to short-term and long-term adverse outcomes for both mothers and infants, clarifying their network structure and core social determinants holds important public health significance for formulating regional intervention strategies. Network analysis is an emerging research tool that intuitively visualizes complex interactive relationships among multiple variables. It overcomes the limitation of traditional regression analysis, which only focuses on the association of a single variable, and can identify core nodes through indicators such as strength and expected influence, thus having unique advantages in analyzing the interactive relationships of complex psychological symptoms. Objective This study aims to explore the associations between emotional symptoms and social determinants in the population of prenatal pregnant women in Xinjiang, China using network analysis, providing new population data and perspectives for research on maternal mental health. Subsequently, it identifies core nodes via centrality analysis, providing a basis for developing multi-dimensional psychological intervention programs for pregnant women in Urumqi, Xinjiang. Methods A convenience sampling method was used to select 1,349 pregnant women who attended obstetric check-ups at a tertiary hospital in Urumqi, Xinjiang, from February 2023 to January 2024 as the research subjects. The inclusion criteria were: (1) aged 18–45 years; (2) clinically confirmed pregnancy by the obstetric department; (3) ability to understand and complete online questionnaires; (4) voluntary participation in this study with verbal informed consent. The exclusion criteria were: (1) pregnant women who refused to complete the questionnaire; (2) those with severe mental disorders or cognitive impairments that prevented them from effectively completing the questionnaire. Data collection was conducted via electronic questionnaires on the Wenjuanxing online survey platform, using a self-designed demographic scale, the Pregnancy Pressure Scale (PPS-30), the Generalized Anxiety Disorder Scale (GAD-7), and the Patient Health Questionnaire (PHQ-9). Results The proportions of pregnant women with prenatal depressive, anxiety, and pregnancy-related stress symptoms were 19.4%, 26.6%, and 92.3% respectively. Other Stressors (strength = 1.21, expected Influence = 1.19), Changes in physical activity (strength = 1.15, expected Influence = 1.15), and Friendship (strength = 1.2, expected Influence = 1.05) were the core nodes of the network. The strongest connections in the emotional symptom subnetwork were Restlessness-Changes in physical activity (weight = 0.17), Difficulty relaxing-stress (Maternal-Infant Health Dimension) (weight = 0.06), and Decreased concentration-stress (Parental Role Dimension) (weight = 0.08). Gestational Period and Friendship, Friendship and Educational Attainment, Relationship with Neighbors and Number of Live Births were the social determinants most strongly associated with depression, anxiety, and pregnancy-related stress respectively. Conclusions This study is the first to systematically reveal the network characteristics of anxiety, depression, and pregnancy-related stress in prenatal women in Urumqi, identifying Other Stressors, Changes in physical activity, and Friendship as the core intervention targets in the network. The results suggest that targeted psychological interventions should focus on stress management and the construction of social support networks, while fully considering the impact of social determinants on intervention effects. These findings provide a theoretical basis and practical guidance for developing more precise and effective perinatal mental health interventions in Urumqi.